Pleurocarpous mosses of Bangladesh : Meteoriaceae and Pterobryaceae (Bangladesh Journal of Plant Taxonomy, 2005)
Barbella rufifolia (Thwait & Mitt.) Broth. (Family Meteoriaceae) and Pterobryopsis auriculata Dix. (Family Pterobryaceae) of Isobryales are described as new records for Bangaldesh. Key words: Pleurocarpous moss; Isobryales; Meteoriaceae; Pterobryaceae; Bangladesh DOI: 10.3329/bjpt.v12i1.611 Bangladesh J. Plant Taxon. 12(1): 53-57, 2005 (June)